The needs of black farm school teachers in relation to using English as the medium of instruction. - Taitz, Lynette (My University, 1992)
The research, conducted as part of a project aimed at improving teachers' English .skills, set out to answer the question: What are the needs of farm school teachers in relation to the use of English as the medium of instruction? Clarification of this question involved the examination of teachers' English proficiency, the teaching of English as a subject and the.observation of the learning/teaching situation in the farm school classroom. The research raised questions concerning the underlying assumption that an English language intervention could bring about major change in the classroom. As a result, further enquiries into the socio-economic context-of the schools were instituted. In addition, the learning/teaching situation was examined in the light of theories of cognition and change. A range of research methods involving both quantitative and qualitative approaches were utilized to penetrate this highly complex situation. The findings indicated a clear need on the. part of ihe teachers for an English proficiency course. At the same time. the findings also indicated most strongly that a fundamental change is needed in tne teachers' understanding of their role if they are to become agents of significant change.
A dissertation submitted to the Faculty of Education, University of the Witwatersrand in fulfillment of the requirements for the degree of Master of Education.
Keywords: Rural schools -- South Africa.; Language and education -- South Africa.; Blacks -- Education -- South Africa.; Teachers, Black -- South Africa.